In Vitro Study of the Antibacterial Effect of Aqueous and Ethanolic Extracts of Citrullus Colocynthis on Streptococcus Mutans and Lactobacillus Acidophilus Bacteria - yasamin barakian; Mohammad Khalife Gholi; hoda Abolhasani; Mahdieh Salman (Mashhad University of Medical Sciences, 2022)
Introduction: Caries happen by the interaction between microorganisms causing caries and carbohydrates on the tooth surface. Studies show the presence of Streptococcus mutans and Lactobacillus acidophilus bacteria in caries lesions. Considering the relative resistance to antibiotics among bacteria and given the antibacterial effect of Citrullus Colocynthis, this study aimed to evaluate the antimicrobial effect of this plant.Materials and Methods: After preparing the extract by the maceration method, serial dilutions of 1:2, in which each concentration contains an active ingredient equal to half of its previous concentration, were prepared from 16384 to 8 µg/ml. Afterward, in each plate, 100 μl of different concentrations of extracts, culture medium (2×), and standard bacterial suspension were added. The plates were incubated in an anaerobic jar at 37°C for 48 h. Following that, minimum inhibitory concentration was determined by observation.Results: Ethanolic extract inhibited the growth of Lactobacillus acidophilus at the concentration of 16384 µg/ml, and the aqueous extract inhibited the growth at the concentrations of 16384 and 8192 µg/ml. The ethanolic and aqueous extracts inhibited Streptococcus mutans growth at the concentrations 16384 and 8192 µg/ml.  Conclusion: The inhibitory effect of ethanolic and aqueous extracts of Citrullus colocynthis on Streptococcus mutans was the same, and considering that only very high concentrations have antibacterial effects, none of the extracts had antibacterial effects on this bacterium. Regarding Lactobacillus acidophilus, none of the extracts had antibacterial effects on this bacterium.